The investigation of ssci indexed studies on problem posing in terms of affective components - ŞENGÜL, SARE (My University, 2022)
The problem posing activities play an important role in students' understanding of mathematical concepts [1]. It has a strategic position in the teaching and learning of mathematics, as it encourages creative thinking and enables the use of existing knowledge [2]. Considering that students' affective characteristics shape mathematics learning outcomes, especially mathematics achievement [3], the need for a holistic analysis of studies that deal with problem posing studies in terms of affective components arises. In this direction, the aim of the research is to examine the general characteristics, aims and results of the studies published in SSCI indexed journals for problem posing in terms of affective components, through a systematic review. Thus, unlike other problem posing studies, the general framework of the related researches, which includes problem posing and affective components, from their aims to results will be drawn and their tendencies will be described and evaluated. The Web of Science database was used in the study and the keywords were determined as "problem posing, mathematics, attitude, self-efficacy, affective factors, motivation". According to the research findings, 19 journal/book/book chapters scanned in the Web of Science where the studies were published were reached. A total of 24 studies, including 15 articles, 7 papers and 2 book/book chapters were examined from the sources reached. More than half of the studies were published between 2018-2020. It has been determined that a small number of studies have been carried out including one study between 2006-2008, 2012-2014 and 2021-2022. Affective areas examined together with problem posing; it has been determined that attitude (f=10) is mostly studied on "attitude, self-efficacy, motivation, anxiety and affective factors", while self-efficacy (f=6) and motivation (f=4) follow the attitude studies quantitatively. The distribution of the studies according to the aims and results is examined in detail and suggestions will be made according to the outputs obtained.
Keywords: Mathematics education; problem posing; affective factors; systematic review